2015
DOI: 10.3109/0284186x.2015.1006401
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of target delineation in laryngeal and hypopharyngeal cancer

Abstract: background and purpose. To determine the spatial correspondence between the gross tumor volume (GTV) delineated on computer tomography (CT) and the actual tumor on histopathology. Material and methods. Sixteen patients with T3 or T4 laryngeal or hypopharyngeal cancer underwent a CT scan before total laryngectomy. The GTV was delineated on CT by three independent observers and by consensus between the three observers. After surgery, whole-mount hematoxylin-eosin stained (H&E) sections were obtained. One patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…2,7,21,22 Recently, Caldas-Magalhaes et al demonstrated that GTVs delineated on CT for laryngeal and hypopharyngeal cancer were 1.7 times larger than the tumor measured on the Hematoxylin-eosin stained pathological sections of the same tumor after surgical resection and registration the respective CT delineations. 23 Also, the first scan utilized could be acquired at an outside hospital with different scanner and different slice thickness than the second scan, which was always done at MD Anderson. This difference may result in error in estimation of comparative tumor volumes.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,21,22 Recently, Caldas-Magalhaes et al demonstrated that GTVs delineated on CT for laryngeal and hypopharyngeal cancer were 1.7 times larger than the tumor measured on the Hematoxylin-eosin stained pathological sections of the same tumor after surgical resection and registration the respective CT delineations. 23 Also, the first scan utilized could be acquired at an outside hospital with different scanner and different slice thickness than the second scan, which was always done at MD Anderson. This difference may result in error in estimation of comparative tumor volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Target delineation, however, is one of the largest sources of uncertainty in head-and-neck cancer radiotherapy [1]. Even with the introduction of new imaging techniques the interobserver variability remains relatively large [2][3][4][5]. For an accurate definition of the target volume, validation of gross tumor volume (GTV) delineation is fundamental.…”
Section: Original Articlementioning
confidence: 99%
“…For this validation, histopathology is the gold standard. However, this validation is a complex procedure and few studies have been performed for head-and-neck cancer [5][6][7]. For radiotherapy purposes, a detailed comparison of histopathology and imaging is required to validate the actual size, shape and location of the tumor.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Target volumes determined on CT and MRI are largely overestimated as shown in pathological validation studies. 1,2 Diffusion-weighted (DW) MRI is a functional imaging technique that provides information on the local mobility of water in tissue. Dense tissues with an increased cellularity, such as glandular and nodal structures or tumors, will restrict the motion of water and show high contrast with surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%